ANALISIS EKSPOR DAN PRODUKSI KARET DI INDONESIA (APLIKASI MODEL LAG TERDISTRIBUSI) - Ahmad Soleh (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2016)
Ahmad Soleh; Export Analysis and Production of Rubber in Indonesia (Distributed Lag Model Application). Contributions plantation sub-sector in the Indonesian economy has a very important role. Rubber is one of the leading commodity exports of Indonesia. Indonesia rubber export volume increase along with the increase in domestic rubber production. This study aimed to examine the relationship between the volume of production for Indonesia rubber export during the period 2000-2014. Sources of data obtained from reports the Central Bureau of Statistics (BPS). The analytical method used is the regression model by using a distributed lag models were processed with the help of Eviews program. As for the lag determination is based on the Schwarz criterion (SC) with the lowest value. The results showed that the relationship between the production of rubber in the country with an export volume of rubber in Indonesia is very high at 93%. Volume Indonesian rubber exports was influenced by the production of rubber in the country within a period of four years. According Koyck model, the time required to change the rubber production in the country has a significant effect and detected in the export volume of 0.5 years. During the observation period, the increase of one tonne of rubber production in the country this year will increase the volume of rubber exports amounted to 0.614898 tons, increase of one tonne of rubber production in the country one year earlier will increase the volume of rubber exports amounted to 0.202631 tons, increase of one tonne of rubber production in the country two years earlier will increase the volume of rubber exports amounted to 0.066774 tons, increase of one tonne of rubber production in the country three years earlier will increase the volume of rubber exports amounted to 0.022004 tons and increase of one tonne of rubber production in the country four years earlier will increase the volume of rubber exports amounted to 0.007251 tons. Government attention is needed in the development of Indonesian rubber production by stabilizing the price of rubber, development and industrial production for processing.Ahmad Soleh; Export Analysis and Production of Rubber in Indonesia (Distributed Lag Model Application). Contributions plantation sub-sector in the Indonesian economy has a very important role. Rubber is one of the leading commodity exports of Indonesia. Indonesia rubber export volume increase along with the increase in domestic rubber production. This study aimed to examine the relationship between the volume of production for Indonesia rubber export during the period 2000-2014. Sources of data obtained from reports the Central Bureau of Statistics (BPS). The analytical method used is the regression model by using a distributed lag models were processed with the help of Eviews program. As for the lag determination is based on the Schwarz criterion (SC) with the lowest value. The results showed that the relationship between the production of rubber in the country with an export volume of rubber in Indonesia is very high at 93%. Volume Indonesian rubber exports was influenced by the production of rubber in the country within a period of four years. According Koyck model, the time required to change the rubber production in the country has a significant effect and detected in the export volume of 0.5 years. During the observation period, the increase of one tonne of rubber production in the country this year will increase the volume of rubber exports amounted to 0.614898 tons, increase of one tonne of rubber production in the country one year earlier will increase the volume of rubber exports amounted to 0.202631 tons, increase of one tonne of rubber production in the country two years earlier will increase the volume of rubber exports amounted to 0.066774 tons, increase of one tonne of rubber production in the country three years earlier will increase the volume of rubber exports amounted to 0.022004 tons and increase of one tonne of rubber production in the country four years earlier will increase the volume of rubber exports amounted to 0.007251 tons. Government attention is needed in the development of Indonesian rubber production by stabilizing the price of rubber, development and industrial production for processing.